A novel biomarker TERTmRNA is applicable for early detection of hepatoma - Miura, Norimasa; Osaki, Yukio; Nagashima, Miki; Kohno, Michimori; Yorozu, Kensho; Shomori, Kohei; Kanbe, Takamasa; Oyama, Kenji; Kishimoto, Yukihiro; Maruyama, Shigeo; Noma, Eijiro; Horie, Yutaka; et al. (BMC gastroenterology, 2010)
Backgrounds We previously reported a highly sensitive method for serum human telomerase reverse transcriptase (hTERT) mRNA for hepatocellular carcinoma (HCC). α-fetoprotein (AFP) and des-γ-carboxy prothrombin (DCP) are good markers for HCC. In this study, we verified the significance of hTERTmRNA in a large scale multi-centered trial, collating quantified values with clinical course. Methods In 638 subjects including 303 patients with HCC, 89 with chronic hepatitis (CH), 45 with liver cirrhosis (LC) and 201 healthy individuals, we quantified serum hTERTmRNA using the real-time RT-PCR. We examined its sensitivity and specificity in HCC diagnosis, clinical significance, ROC curve analysis in comparison with other tumor markers, and its correlations with the clinical parameters using Pearson relative test and multivariate analyses. Furthermore, we performed a prospective and comparative study to observe the change of biomarkers, including hTERTmRNA in HCC patients receiving anti-cancer therapies. Results hTERTmRNA was demonstrated to be independently correlated with clinical parameters; tumor size and tumor differentiation (P < 0.001, each). The sensitivity/specificity of hTERTmRNA in HCC diagnosis showed 90.2%/85.4% for hTERT. hTERTmRNA proved to be superior to AFP, AFP-L3, and DCP in the diagnosis and underwent an indisputable change in response to therapy. The detection rate of small HCC by hTERTmRNA was superior to the other markers. Conclusions hTERTmRNA is superior to conventional tumor markers in the diagnosis and recurrence of HCC at an early stage.